Measuring Corruption: Whose Perceptions Should We Rely On? : Evidence from Iceland - Erlingsson, Gissur Ó (Veftímaritið Stjórnmál og stjórnsýsla, 2016)
The extent of corruption in Iceland is highly contested. International corruption measures indicate a relatively small amount of corruption, while domestic public opinion suggest a serious corruption problem. Thus, uncertainty prevails about the actual extent of corruption and whose perceptions to rely on. This problem is relevant for corruption research in general. Perceptions are increasingly used as proxies for the actual levels of corruption in comparative research. But we still do not know enough about the accuracy of these proxies or the criteria they must meet in order to give dependable results. In fact, radical differences exist concerning evaluations of perceptions between those who believe in unbiased learning and those believing perceptual bias to be widespread. The purpose of this article is, therefore, to attempt to gauge which factors may influence how perceptions of corruption are shaped and why differences in corruption perceptions between different groups may be so pronounced. We present findings from original survey data from three parallel surveys – among the ‘public’, experts, and ‘municipal practitioners’ – conducted in Iceland in 2014. Expectations based on the perceptual bias approach are tested, indicating that perceptions may be affected by (1) information factors, (2) direct experience of corruption and (3) emotive factors. The validity of perception measures should be considered with this in mind. Domestic experts are likely to be well informed and avoid perceptual bias to a greater extent than other groups. Our examination of the Icelandic case suggests that the Corruption Perception Index (CPI) tends to underestimate corruption problems in ‘mature welfare states’, such as Iceland, whilst the general public tends to overestimate it.